2002
DOI: 10.1093/heapol/17.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Cost of access to health services in Zambia

Abstract: Equity is an important policy objective in the health care field. The importance of equity in health care provision can be argued from various points of view. As a result governments in all countries attempt to provide health care systems that enable equal access for everyone. Zambia is no exception. In the health care reforms the objective of the national health strategy is to provide Zambians with equity of access to health care. We focus on access defined as the costs (both monetary and time) an individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 5 publications
2
48
2
Order By: Relevance
“…The rural dwellers, who already live in resource poor environment and are mostly subsistence farmers, pay twice the amount the urban dwellers pay as transport cost while seeking health for their children suffering from malaria. In developing countries where distances to health facilities can be large, the infrastructure lacking and a large share of the population live below the poverty line, cost of access is a critical determinant of whether care is sought or not [41].…”
Section: Discussionmentioning
confidence: 99%
“…The rural dwellers, who already live in resource poor environment and are mostly subsistence farmers, pay twice the amount the urban dwellers pay as transport cost while seeking health for their children suffering from malaria. In developing countries where distances to health facilities can be large, the infrastructure lacking and a large share of the population live below the poverty line, cost of access is a critical determinant of whether care is sought or not [41].…”
Section: Discussionmentioning
confidence: 99%
“…It can be deduced from this observation that if cost is a barrier to primary health care use, one direct effect is that the cost effectiveness of interventions will be reduced and the costs of malaria intervention will in the long run increase. According to Hjortsberg and Mwikisa (2002), reduced effectiveness of health care interventions is attributed to among other things, existing barriers that prevent consumers from using health care.…”
Section: Figure 1: Proportions Of Respondents and Their Perceptions Omentioning
confidence: 99%
“…According to Hjortsberg and Mwikisa (2002), cost of access creates an especially problematic barrier to the poor people who need to seek care. It is further argued that in developing countries where distances to health facilities can be large, the infrastructures lacking and large number of people living below the poverty line, cost of access is a critical determinant of whether care is sought or not.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to UHC in Zambia, the major obstacle reported were long distances to health facilities especially during the rain farming seasons (Hjortsberg et al, 2002). In public health facilities it was reported that the rich had better access to the hospitals and the poor used primary health care facilities.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a disparity between the scope and quality between rural and urban services with the latter getting better services (Hjortsberg et al, 2002). The PHC approach has remarkably improved health services in some areas but not to level of attaining universal health coverage (UHC) (Yach, 1997).…”
Section: Introductionmentioning
confidence: 99%